2022
DOI: 10.1002/hsr2.477
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and heart rate monitoring of nurses using PPG and ECG signals during working condition: A pilot study

Abstract: The use of wearable photoplethysmography (PPG) technology for estimating heart rate (HR) and HR variability (HRV) in the health care system is gaining attention in recent years. However, the performance of these devices remains questionable in their ability to collect data in real working conditions for long-term monitoring. The present study aimed to examine the data collected from nurses during working hours by PPG and electrocardiography (ECG) devices. Twenty-two nurses underwent a 60-minute work protocol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…PPG can be implemented on a variety of body sites including earlobes, finger tips, wrist, and neck; it eliminates wires by using an optical method to predict HR based on blood oxygenation [16] , [29] . Historically the clinical gold standard for HR and HRV has been ECG [11] , [17] , but many studies have found that PPG derived HRV values are acceptably close to those of ECG [16] , [29] , [30] . Both PPG and ECG have been shown to be useful in deriving RR and BVP, with PPG being slightly better for BVP [31] , [32] , [33] .…”
Section: Hardware Descriptionmentioning
confidence: 99%
“…PPG can be implemented on a variety of body sites including earlobes, finger tips, wrist, and neck; it eliminates wires by using an optical method to predict HR based on blood oxygenation [16] , [29] . Historically the clinical gold standard for HR and HRV has been ECG [11] , [17] , but many studies have found that PPG derived HRV values are acceptably close to those of ECG [16] , [29] , [30] . Both PPG and ECG have been shown to be useful in deriving RR and BVP, with PPG being slightly better for BVP [31] , [32] , [33] .…”
Section: Hardware Descriptionmentioning
confidence: 99%
“…[19][20][21][22] Heart rate variability (HRV) has been used in research to measure the negative health effects of shift work, 23 the benefits of aromatherapy 24 and the efficacy of using photoplethysmography compared with electrocardiography in nursing populations. 25 The fluctuating heart rate of a normally regulated person will show high HRV when responding to a stressful event. 22 For people who have been exposed to childhood trauma, chronic stress and/ or disease, HRV may be low and dysregulated indicating an impaired ANS response to stressors.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%